Rivulus hartii (Boulenger 1890) (Cyprinodontiformes: Rivulidae): ESPECIE DE PEZ DULCEACUÍCOLA AMENAZADA EN LA ISLA DE MARGARITA, VENEZUELA - Nirchio, Mauro; Gómez H., Juan A.; Oliveira, Claudio; Ron, Ernesto; Nirchio, Mauro J.; Villaroel, José (Tecnociencia, 2005)
Sin resumen